Did COVID-19 induce a reallocation wave? - Agostino Consolo; Filippos Petroulakis (European Central Bank (ECB), 2022)
Recent research has argued that the COVID-19 shock has also brought about a reallocation shock. We examine the evidence for such an occurrence in the United States, taking a broad perspective. We first consider micro data from CPS and JOLTS; there is no noticeable uptick in occupation or sector switches, nor churn, either at the aggregate level or the cross-section, or when broken down by firms' s ize. We then examine whether mismatch unemployment has risen as a result of the pandemic; using an off-the-shelf multisector search and matching model, there is little evidence for an important role for mismatch in driving the elevated unemployment rate. Finally, we employ a novel Bayesian SVAR framework with sign restrictions to identify a reallocation shock; we find that it has played a relatively minor role in explaining labor market patterns in the pandemic, at least relative to its importance in earlier episodes.
Keywords: E24; J63; 330; Reallocation; COVID-19; mismatch